2015
DOI: 10.18632/oncotarget.2865
|View full text |Cite
|
Sign up to set email alerts
|

RACK1is a candidate gene associated with the prognosis of patients with early stage non-small cell lung cancer

Abstract: BackgroundThis study was conducted to identify genetic polymorphisms associated with the prognosis of patients with early stage NSCLC.Materials and MethodsWe genotyped 1,969 potentially functional single nucleotide polymorphisms (SNPs) of 1,151 genes involved in carcinogenesis in 166 NSCLC patients who underwent curative surgery, using the Affymetrix custom-made GeneChip. A replication study was performed in an independent cohort of 626 patients.ResultsFifty six SNPs which were associated with both overall sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 40 publications
(36 reference statements)
0
20
0
Order By: Relevance
“…It has been suggested in previous studies that the dysregulation of RACK1 is involved in a variety of cancers, such as esophageal squamous cell carcinoma, lung cancer and ovarian cancer (10)(11)(12)(13). In the study by Peng et al, it was demonstrated that the enforced downregulation of RACK1 inhibited tumor xenograft growth in nude mice, and inhibited the proliferation and invasion of human glioma cells in vitro (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested in previous studies that the dysregulation of RACK1 is involved in a variety of cancers, such as esophageal squamous cell carcinoma, lung cancer and ovarian cancer (10)(11)(12)(13). In the study by Peng et al, it was demonstrated that the enforced downregulation of RACK1 inhibited tumor xenograft growth in nude mice, and inhibited the proliferation and invasion of human glioma cells in vitro (14).…”
Section: Discussionmentioning
confidence: 99%
“…The receptor for activated C kinase 1 (RACK1) is a versatile scaffold protein involved in the regulation of a variety of cellular processes, including cell growth, migration, survival and metastasis (7)(8)(9). Previous studies have indicated that RACK1 is abnormally expressed in various malignant tumors, and its dysregulation may contribute to tumorigenesis (10)(11)(12)(13). Certain pathways have been demonstrated to be activated by RACK1, such as the Src/Akt signaling pathway, mitogen-activated protein kinase (MAPK) signaling pathway, and the sonic hedgehog signaling pathway (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, promoter assay and electrophoretic mobility shift assay (EMSA) revealed that the rs3756585 T‐to‐G change increased transcription factor binding and promoter activity of GNB2L1 . This study suggests that polymorphisms of the two genes enhance the prognostic ability of pathologic stage in the novel prognosis‐prediction model. Further studies are needed to understand the roles of the two genes in lung cancer and to clarify the association between the SNPs and prognosis.…”
Section: Discussionmentioning
confidence: 70%
“…We selected SNPs for the present study using public databases, as described previously [13,14]. Briefly, we selected 1784 candidate genes involved in cancer-related pathways from the database of SABiosciences (www.sabiosciences.com/Cancer.php; online supplementary table S1).…”
Section: Selection Of Polymorphisms and Genotypingmentioning
confidence: 99%